Comparing the Difference on Inflow of Patients in Oral and Maxillofacial Surgery Department before and During Covid-19 - Vishal, Rampershad, Ali Raza, Ghulam Nabi Memon, Muhammad Waleed Vohra, Suneel Kumar Punjabi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To Compare the difference on the inflow of patients before and during COVID-19 on the patients presented at oral & maxillofacial surgery at Advance Dental Care Centre, Liaquat University of Medical and Health Sciences Materials &Methods: Medical statistics have been collected for the patients who visited the Advance dental care centre, Liaquat university of medical and health sciences between 1 January 2019 and 31 December 2020. The data collected included age, gender, and extraction of teeth. SPSS version 20.0 was used for the statistical analysis. Results: Of all the patients who visited, 3715 were females and 2571 were males, with a female to male ratio of 1.2:1. The youngest patient was 15 years old, and the oldest was 60 years old. The most common cause among patients in 2019 and 2020 was periodontal problems. Conclusion: The COVID-19 epidemic affected the population, pattern of oral diseases, its services, and the frequency of visits to advance dental care centre the proportions of patients who were adolescents and elderly people increased, meanwhile the percentage of the conservative treatments increased during the outbreak of COVID-19. Keywords: COVID -19, Tooth extraction; Periodontal disease, Prophylactic antibiotics.